Switzerland : Technical Note-Oversight, Supervision, and Risk Management of Financial Market Infrastructures. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This Technical Note on Oversight, Supervision, and Risk Management of Financial Market Infrastructures explains that financial market infrastructures (FMIs) in Switzerland are well-developed and stable. The FMIs operate smoothly for many years without any substantial outage or other technical or financial problem. Payment in Swiss francs, both large value and retail payments, are settled in the Swiss Interbank Clearing, which is a real time gross settlements system. Important progress has been realized regarding the adoption of the new principles for FMIs. FMIs should continue their efforts to achieve full compliance. The new Swiss Financial Market Infrastructure Act should be passed by Parliament to complete the process. Although the risk management framework of SIX Group AG is comprehensive it has certain gaps that need to be addressed to fully observe the new international standards. The Swiss National Bank (SNB) and Financial Market Supervisory Authority (FINMA) are encouraged to hold a firm stance on the full implementation of the new principles in Switzerland. The SNB and FINMA should upgrade their domestic and foreign cooperation arrangements to be able to handle crisis events effectively and in a timely manner. The domestic cooperation arrangements work well in normal circumstances but may prove insufficient during crisis events in the absence of a lead supervisor or overseer of the FMIs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet